ANALISIS FOOD CONVERSION RATIO (FCR) IKAN NILA (OREOCHROMIS NILOTICUS) PADA SISTEM KERAMBA JARING APUNG DI DANAU BATUR - Kadek Yogi Anugerah Prawira Darma; Gede Iwan Setiabudi; Alexander Korinus Marantika (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Nile tilapia (Oreochromis niloticus) is a leading commodity in Lake Batur; however, its production sustainability is challenged by fluctuations in feed efficiency among farmers. This study aims to analyze production performance, particularly Feed Conversion Ratio (FCR) and Survival Rate (SR), spatially and to identify the technical and biological factors influencing them. A descriptive quantitative method with an ex-post facto approach was applied to 20 farmers across four regions (West, East, North, and South). The One-Way ANOVA test results indicated significant differences (p < 0.05) in FCR values among locations. The western region showed the best efficiency (FCR 1.06 ± 0.18; SR 66%), while the eastern region recorded the lowest (FCR 1.39 ± 0.03). Regression analysis revealed that rearing duration had a significant effect (p = 0.010), indicating the role of natural feed such as periphyton. Inefficiency in the eastern region was associated with phantom feeding due to high initial mortality. Recommended strategies include improved seed management, optimization of natural feed, and periodic fasting practices.